Non-linear dynamics of oil supply news shocks - Mirela Miescu; Haroon Mumtaz; Konstantinos Theodoridis (Cardiff University, Cardiff Business School, 2024)
This paper employs Threshold (T)VAR models to investigate the asymmetric impact of oil supply news shocks, analysing variations in both the size and direction of the shocks. Our findings reveal that large and adverse oil shocks exert a stronger effect on real activity, labour market indicators, and risk variables compared to small and favourable shocks. Interestingly, we observe no asymmetry in the response of prices and monetary policy to oil shocks of different magnitudes and signs. Using a theoretical nonlinear model and predictive prior analysis, we demonstrate that search and matching labour frictions cause the risk of becoming unemployed to increase after an oil shock. This rise in unemployment risk triggers strong precautionary savings motives, which increase with the size of the shock, leading to asymmetric responses in real economic and labour market variables, whereas price indicators and the policy rate do not exhibit such nonlinearities consistently with the empirical findings.
Keywords: 330